TYPES OF RELIGIOUS TERM IN THE BOOK "ISLAM: A SHORT HISTORY" - Mujazin, Mujazin; Nababan, M. R.; Santosa, Riyadi; Wibowo, Agus Ari (English Language and Literature International Conference (ELLiC) Proceedings, 2019)
Religious terms are the terms and expressions whose source is obtained anddominated by the book of one religion or more. This research aims at exploring the religious terms and expressions found in the book of "Islam: A Short History", their types, meanings, and examples of religious term and expression. This article is qualitative research in which the researcher explains the types and examples of the religious terms found in the book. There are 14 religious terms (10 from Newmark, 1 from Alghamdy, and 3 from Yulianita) that have been found in previous studies, but those (14) above have not covered all the religious terms in the book. After researching the book of Islam: A Short History, the researcher found 1 (one) new term needed to be included in order to accommodate all religious expressions, so it’s 15 after all. This 1 new religious term (owner of the religion) is the split from the previous term (supernatural being). It is separated because of the mismatch between the type and example. Moreover, after the research, religious terms are classified into two, namely Arabic and non-Arabic. They are classified based on how much impact of the Arabic gives to the religious term.